ADDRESSING THE NEEDS OF NURSING HOMES USING MULTIPLE APPROACHES TO EDUCATION AND SUPPORT. (20th December 2022) - Cotton, Sam; Faul, Anna; Yankeelov, Pamela; Gordon, Barbara; Magnuson, Justin; Henage, Cris; Hubbard, Jennifer; Roberts, Ellen
Abstract: At the University of Louisville and University of North Carolina Geriatric Workforce Enhancement Programs (GWEPs), we have collaborated to develop and implement a multi-faceted program to training to address the pressing challenges within NHs and foster community. We have created a Project ECHOs series for NH administers and nursing staff to foster support, while providing education on critical topics including age-friendly healthcare, vaccine hesitancy and infectious disease control, and ways to address health disparities. Additionally, we have developed videos for CNAs and direct support staff. For NH residents and families, we are designing education and offering services to address the disparities related to mental health needs. The UofL and UNC GWEPs mission is to provide a more holistic approach to NH care and opportunities for support and community. Implications for changes in policy and future practice within NHs and the use of collaborative approaches will be discussed.